2009
DOI: 10.5194/acp-9-5785-2009
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from biomass burning in the Yucatan

Abstract: Abstract. In March 2006 two instrumented aircraft made the first detailed field measurements of biomass burning (BB) emissions in the Northern Hemisphere tropics as part of the MILAGRO project. The aircraft were the National Center for Atmospheric Research C-130 and a University of Montana/US Forest Service Twin Otter. The initial emissions of up to 49 trace gas or particle species were measured from 20 deforestation and crop residue fires on the Yucatan peninsula. This included two trace gases useful as indic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
617
9

Year Published

2014
2014
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 497 publications
(680 citation statements)
references
References 97 publications
54
617
9
Order By: Relevance
“…However, the trend of increasing f 44 in fresh plumes suggests that this processing can occur over very short timescales under certain atmospheric conditions. Rapid oxidation of BB smoke plumes has previously been inferred from the addition of secondary OA mass within ∼ 1 h of emission Yokelson et al, 2009), corroborating the BORTAS trend. Values of f 44 coinciding with peak concentrations for a number of combustion products are also shown in Fig.…”
Section: Campaign Intercomparison and Evaluation Of F 44supporting
confidence: 69%
See 1 more Smart Citation
“…However, the trend of increasing f 44 in fresh plumes suggests that this processing can occur over very short timescales under certain atmospheric conditions. Rapid oxidation of BB smoke plumes has previously been inferred from the addition of secondary OA mass within ∼ 1 h of emission Yokelson et al, 2009), corroborating the BORTAS trend. Values of f 44 coinciding with peak concentrations for a number of combustion products are also shown in Fig.…”
Section: Campaign Intercomparison and Evaluation Of F 44supporting
confidence: 69%
“…Concentrations of trace gases primarily produced by fire sources, including HCN and CH 3 CN, are commonly used as indicators for BB plumes (Li et al, 2000;Yokelson et al, 2007;Crounse et al, 2009;Yokelson et al, 2009;Akagi et al, 2011). A scheme using a HCN concentration threshold of six times the standard deviation (6σ ) has been used during BORTAS in an analysis of high sensitivity 1 Hz CIMS measurements and their consistency with CO and CH 3 CN concentrations (Le Breton et al, 2013).…”
Section: Data Selectionmentioning
confidence: 99%
“…However, it does not preclude that there was significant net OA production/evaporation that occurred prior to or after this observed period as has been observed in other BB field studies (e.g. Akagi et al, 2012;Yokelson et al, 2009). Thus, although evidence of photo-oxidation and chemical processing was observed in-plume by Parrington et al (2013), any chemical composition impact on the size distribution at the ages observed here seems negligible.…”
Section: Net Production/loss Of Organic Aerosol With Timementioning
confidence: 44%
“…Coagulation is a driving factor in size-distribution evolution due to the high concentrations of particles within plumes (Andreae and Merlet, 2001;Capes et al, 2008). Production of secondary organic aerosol (SOA) in-plume has been observed in chamber studies Grieshop et al, 2009;Hennigan et al, 2011;Heringa et al, 2011;Ortega et al, 2013) and in the field (DeCarlo et al, 2010;Lee et al, 2008;Reid et al, 1998;Yokelson et al, 2009), and this SOA will condense onto the particles, increasing their size. In addition, the primary organic aerosol (POA) emitted by the fires may evaporate during the dilution of the plume (Huffman et al, 2009;May et al, 2013).…”
Section: Biomass-burning Particlesmentioning
confidence: 99%
“…Recent research has become increasingly focused on less-well-studied APNs due to their involvement in several key atmospheric processes. Of these, interest has been generated for acryloyl peroxynitrate (APAN, CH 2 CHC(O)O 2 NO 2 ), a product of acrolein oxidation, where the dominant atmospheric source is understood to be from aged biomass burning emissions (Yokelson et al, 2009). Methacryloyl peroxynitrate (MPAN, CH 2 C(CH 3 )C(O)O 2 NO 2 ) has received recent attention due to its involvement as an intermediate in secondary organic aerosol formation from isoprene (Surratt et al, 2010).…”
Section: Introductionmentioning
confidence: 99%